Matching Participants for Triceps Surae Muscle Strength and Tendon Stiffness Does Not Eliminate Age-Related Differences in Mechanical Power Output During Jumping - König, Matthias; Hemmers, Svenja; Epro, Gaspar; McCrum, Christopher; Ackermans, Thijs Maria Anne; Hartmann, Ulrich; Karamanidis, Kiros (Frontiers in Physiology, 2018)
Reductions in muscular power output and performance during multi-joint motor tasks with ageing have often been associated with muscle weakness. This study aimed to examine if matching younger and middle-aged adults for triceps surae muscle strength and tendon stiffness eliminates age-related differences in muscular power production during drop jump. The maximal ankle plantarflexion moment and gastrocnemius medialis tendon stiffness of twenty-nine middle-aged (40 - 67 years) and twenty-six younger (18 - 30 years) healthy physically active male adults were assessed during isometric voluntary ankle plantarflexion contractions using simultaneous dynamometry and ultrasonography. The elongation of the tendon during the loading phase was assessed by digitizing the myotendinous junction of the gastrocnemius medialis muscle. Eight younger (23±3 y) and eight middle-aged (54±7 y) adults from the larger subject pool were matched for triceps surae muscle strength and tendon stiffness (plantarflexion moment young: 3.1±0.4 Nm/kg; middle-aged: 3.2±0.5 Nm/kg; tendon stiffness: 553±97 vs. 572±100 N/mm) and then performed series of drop jumps from different box heights (13, 23, 33 and 39 cm) onto a force plate (sampling frequency 1000 Hz). The matched young and middle-aged adults showed similar drop jump heights for all conditions (from lowest to highest box height: 18.0±3.7 vs. 19.7±4.8 cm; 22.6±4.2 vs. 22.9±4.9 cm; 24.8±3.8 vs. 23.5±4.9 cm; 25.2±6.2 vs. 22.7±5.0 cm). However, middle-aged adults showed longer ground contact times (on average 36%), lower vertical ground reaction forces (36%) and hence lower average mechanical power (from lowest to highest box height: 2266±563 vs. 1498±545 W; 3563±774 vs. 2222±320 W; 4360±658 vs. 2475±528 W; 5008±919 vs. 3034±435 W) independent of box height. Further, leg stiffness was lower (48%) in middle-aged compared to younger adults for all jumping conditions and we found significant correlations between average mechanical power and leg stiffness (0.70 ≤ r ≤ 0.83; p < 0.01). Thus, while jumping performance appears to be unaffected when leg extensor muscle strength and tendon stiffness are maintained, the reduced muscular power output during lower limb multi-joint tasks seen with ageing may be due to age-related changes in motor task execution strategy rather than due to muscle weakness.